HAK NAFKAH, MASKAN DAN KISWAH SELAMA DALAM IDDAH TERHADAP BEKAS ISTRI YANG TELAH DICERAI TALAQ DALAM KEDUDUKANNYA QOBLA DUKHUL (Study Putusan Pengadilan Agama Rantauprapat No. 1173/Pdt.G/2020/PA.RAP) - Aisyah Aisyah (Jurnal Ilmiah Advokasi, 2020)
This study aims to analyze the legal aspects of Mut ah Rights and Eid al-Fitr towards the wife who has been divorced by Talaq in her position as Qobla Dukhul. This research is Normative Empirical, namely research by looking at the existing conditions in the field by linking the legal sources of regulations in force in the Republic of Indonesia. The benefits that will be received from the results of this research are to find out and analyze the legal basis of Mut ah Rights and Iddah livelihoods against a wife who has been divorced by her husband in her position that the wife has not been interfered with at all (Qobla Dukhul) and to know and analyze legal considerations in the decision. Rantauprapat Religious Court No. 1173 / Pdt.G / 2020 / PA.RAP for Divorce talaq in the position of wife of Qobla Dukhul. The results of this study state that if a marriage breaks up due to divorce, according to the provisions of Article 149 and Article 158 of the Compilation of Islamic Law, the ex-husband is obliged to give a proper mutÊ»ah to his ex-wife, either in the form of money or objects, unless the former wife is qobla al dukhul and provides a living , maskan and kiswah to the ex-wife during iddah, unless the ex-wife has been through divorce ba1in or Nusyuz and is not pregnant. In the consideration of the Panel of Judges in Case No. 1173 / Pdt.G / 2020 / PA.RAP stated that because the marriage broke up due to divorce in the Qabla ad-Dukhul State, the Respondent did not have a period of iddah at all and the applicant was released from all legal consequences of divorce such as providing support, maskan and kiswah to ex-wife during iddah.Keywords: Mut'ah, Nafkah Iddah, Qobla DukhulÂ